TRPM4 inhibitor 9‐phenanthrol activates endothelial cell intermediate conductance calcium‐activated potassium channels in rat isolated mesenteric artery - Garland, C; Smirnov, S; Bagher, P; Lim, C; Huang, C; Mitchell, R; Stanley, C; Pinkney, A; Dora, K (Wiley, 2014)
Background and Purpose: Smooth muscle transient receptor potential melastatin 4 (TRPM4) channels play a fundamental role in the development of the myogenic arterial constriction that is necessary for blood flow autoregulation. As TRPM4 channels are present throughout the vasculature, we investigated their potential role in non‐myogenic resistance arteries using the TRPM4 inhibitor 9‐phenanthrol. Experimental Approach: Pressure and wire myography were used to assess the reactivity of rat arteries, the latter in combination with measurements of smooth muscle membrane potential. Immunohistochemistry (IHC) and endothelial cell (EC) calcium changes were assessed in pressurized vessels and patch clamp measurements made in isolated ECs. Key Results: The TRPM4 inhibitor 9‐phenanthrol reversibly hyperpolarized mesenteric arteries to circa EK and blocked α1‐adrenoceptor‐mediated vasoconstriction. Hyperpolarization was abolished and vasoconstriction re‐established by damaging the endothelium. In mesenteric and cerebral artery smooth muscle, 9‐phenanthrol hyperpolarization was effectively blocked by the KCa3.1 inhibitor TRAM‐34. 9‐Phenanthrol did not increase mesenteric EC [Ca2+]i, and Na+ substitution with N‐methyl‐D‐glucamine only increased the muscle resting potential by 10 mV. Immunolabelling for TRPM4 was restricted to the endothelium and perivascular tissue. Conclusions and Implications: These data reveal a previously unrecognized action of the TRPM4 inhibitor 9‐phenanthrol – the ability to act as an activator of EC KCa3.1 channels. They do not indicate a functionally important role for TRPM4 channels in the reactivity of non‐myogenic mesenteric arteries.